Designing the Market for Job Vacancies: A Trust Experiment with Employment Centers Staff - Guglielmo Briscese; Andreas Leibbrandt (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Trust is a key factor for the well-functioning of labor markets. We experimentally study the behavior of staff at competing employment agencies who serve as matchmakers between labor supply and demand. Employment agents can collaborate by sharing vacancies and job seekers at the risk of the other agent approaching the employer to place their own job seekers. In a framed field experiment with actual employment agents we test mechanisms to increase collaboration. We find that financial incentives to collaborate increase vacancy sharing but also increase the likelihood of the other provider approaching the employer to place their own job seekers. We also find that social incentives can backfire and decrease vacancy sharing unless employment agents have a perfect reputation. However, social incentives have a positive effect in increasing cooperative behavior. We discuss the implications for the design of incentives to increase trust in competitive markets like that of employment agencies.
Keywords: D90; C92; J48; 330; trust game; labor market; framed field experiment